Influence of independent bent-up bars on the shear capacity of reinforced concrete beams - Saleh Baras, Saleh Abdullah (2013)
Reinforced concrete beams are designed to resist bending due to applied moments; however it is equally important to design them for shear in order to avoid sudden failure due to shear forces. This paper aims at studying the effectiveness and feasibility of the use of independent bent-up bars systems as shear reinforcement. The proposed systems are to replace the conventional stirrups and stand alone as shear reinforcement. The effect of different parameter involved in the shear phenomenon were reviewed in order to better understand the behavior of reinforced concrete beams when exposed to shearing forces. For verification, a beam with conventional stirrups was used as a control specimen to which the results obtained were compared. As was expected, all the proposed systems provided better shear resistance than the control; beam, this can be seen by the maximum loads at which they failed, the less cracks formed in the shear spans and by the type of failure where they all failed in bending except for specimen B6. B1 failed at load 220 kN, this beam was the control beams reinforced in shear with R6-50mm links. B2, B3, B4, B5 and B6 failed at 245kN, 230kN, 230kN, 240kN and 240kN, respectively. Specimen B2 was reinforced with least amount of shear reinforcement of all the specimens, about 20 percent less than the control specimen, yet showed the highest resistance and the highest ductility where it failed at load 240kN and a maximum deflection of 24.51mm. Similarly specimen B4 failed at 230 kN and had relatively high ductility where the maximum deflection occurred at failure was 21.71mm. On the other hand B3, B5 and B6 still provided more shear resistance than the control beam, however showed very low ductility where the beams failed at maximum deflections of 10.5mm, 9.91mm and 10.22mm, respectively. All in all, independent bent-up bar systems are effective in resisting shear and hence; should be used on their own and not only if combined with stirrups